Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, Ukuran Perusahaan Terhadap Kinerja Keuangan Dimoderasi Struktur Modal - Malau, Clara Nova Augustina; Sani, Ahmad; Ika, Desi (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study aims to determine the effect of managerial ownership, institutional ownership and firm size on financial performance with capital structure as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange in 2017 - 2021. The sample selection method used is purposive sampling. The total observations in this study were 115 samples consisting of 23 companies. The data analysis technique used in this study is Moderated Regression Analysis (Interaction Test) using the SPSS 26 analysis tool. The results of this study indicate that managerial ownership, institutional ownership, firm size and capital structure simultaneously affect on financial performance. Partially, institutional ownership has a positive influence on financial performance, while managerial ownership and firm size have no influence on financial performance. Capital structure is able to moderate and strengthen the relationship between firm size on financial performance, while capital structure is unable to moderate the effect of managerial ownership and institutional ownership on financial performance.